Inspeção no palacio de la luz – Montevideo: uma visão de durabilidade - Medeiros, M. H. F.; Giordano, D. E.; Pereira, E.; Vignolo, A.; Galeano, R.; Helene, P. (Revista ALCONPAT, 2012)
The "Palacio de La Luz" is a building designed by architect Fresnedo Siri and was inaugurated in 1948 in Montevideo, Uruguay. After more than six decades in service, this structure required a corrective action due to cracks and water infiltration problems in the facades, which required an inspection and diagnosis to obtain adequate subsidies for the correct preparation of the rehabilitation project. This work of inspection and diagnosis was made in two stages of its service life, the first being in October 2004 and the second in January 2009. The aim of this paper is to present a comparison of results obtained in the two inspections, allowing to evaluate the evolution of the phenomena of degradation that occurred during those five years apart. The conclusions are that the structural columns are not compromised, decorative pillars need immediate recovery and the rate of carbonation of the concrete of the Palacio de La Luz has accelerated in recent years.Key words: inspection; diagnosis; reinforced concrete; corrosion.